PERAN GURU PENDIDIKAN AGAMA KATOLIK DALAM MENEGAKKAN DISIPLIN SISWA KELAS VII SMP RK DELI MURNI DELITUA - Tibo, Paulinus; Br Munthe, Yelly Yuwindawati (Jurnal Bahasa Indonesia Prima (BIP), 2023)
This research was conducted to determine the role of Catholic religious education teachers in enforcing the discipline of class VII students at SMP RK Deli Murni Delitua. This study uses a qualitative method. The qualitative method was chosen because it can explore a problem in depth and can explain in detail  problem that occurs, starting from identifying a problem to explaining the solution. This study used several techniques o collect the data  namely interviews, observation, and documentation. The research subject used were 1 tutor, 1 school principal, 1 colleague, and 6 students of class VII junior high school. The results of this study indicate that there are still students who do not obey the rules set by the school,students who skip school, students who come late to school, and student who smoke at school. Researchers found that the role of Catholic religious education teachers in upholding student discipline was good. Learning the Catholic religion implies that discipline is the main requirement to obey the rules. The contribution to the school is with the role of the Catholic religious education teacher as a good educator.